Neuroprotective Effect of Non-viral Gene Therapy Treatment Based on Tetanus Toxin C-fragment in a Severe Mouse Model of Spinal Muscular Atrophy - Oliván, Sara; Calvo, Ana C.; Rando, Amaya; Herrando-Grabulosa, Mireia; Manzano, Raquel; Zaragoza, Pilar; Tizzano, Eduardo F.; Aquilera, Jose; Osta, Rosario (Frontiers in Molecular Neuroscience, 2016)
Spinal muscular atrophy (SMA) is a hereditary childhood disease that causes paralysis and progressive degeneration of skeletal muscles and spinal motor neurons. SMA is associated with reduced levels of full-length Survival of Motor Neuron (SMN) protein, due to mutations in the Survival of Motor Neuron 1 gene. Nowadays there are no effective therapies available to treat patients with SMA, so our aim was to test whether the non-toxic carboxy-terminal fragment of tetanus toxin heavy chain (TTC), which exhibits neurotrophic properties, might have a therapeutic role or benefit in SMA. In this manuscript, we have demonstrated that TTC enhance the SMN expression in motor neurons “in vitro” and evaluated the effect of intramuscular injection of TTC-encoding plasmid in the spinal cord and the skeletal muscle of SMNdelta7 mice. For this purpose, we studied the weight and the survival time, as well as, the survival and cell death pathways and muscular atrophy. Our results showed that TTC treatment reduced the expression of autophagy markers (Becn1, Atg5, Lc3 and p62) and pro-apoptotic genes such as Bax and Casp3 in spinal cord. In skeletal muscle, TTC was able to downregulate the expression of the main marker of autophagy, Lc3, to wild type levels and the expression of the apoptosis effector protein, Casp3. Regarding the genes related to muscular atrophy (Ankrd1, Calm1, Col19a1, Fbox32, Mt2, Myod1, NogoA, Pax7, Rrad, and Sln), TTC suggest a compensatory effect for muscle damage response, diminished oxidative stress and modulated calcium homeostasis. These preliminary findings suggest the need for further experiments to depth study the effect of TTC in SMA disease.